The association of age, gender, education and employment status with potential acceptance of a COVID-19 vaccine in Southern Kerala, India - Roy, Layana; Mathew, Seara M.; Raju, Christin V.; Joseph, Hannah; K. S., Jayakumar; James, Roshiny Thankam (International Journal Of Community Medicine And Public Health, 2022)
Background: Coronavirus disease 2019 (COVID-19) pandemic has affected most the countries causing a devastating influence on world health and economics since its appearance. The accelerated development of the COVID-19 vaccine has become vital, and early data suggests that it is both, safe and efficacious. However, the acceptance of the COVID-19 vaccine depends on several socio-demographic characteristics as well as people’s knowledge and misconceptions. The objective of current study was to access the associations of age, gender, and level of education with vaccine acceptance, from a random sample of 525 participants selected from Kerala, India. Methods: This is a cross-sectional study conducted by analyzing the data collected through a self-administered questionnaire that was shared online and directly across southern Kerala from January 2021 to June 2021. The survey questionnaire consisted of demographic characteristics of the respondents and queries pertaining to knowledge and acceptance of the COVID-19 vaccine. Results: The results of the study showed that the respondents showed a good level of knowledge and acceptance. We conducted this study to understand the attitudes towards COVID-19 vaccines and hesitancy to accept it based on age, gender and educational classification. The age group 18-38 has highest rate of acceptance. A higher rate of acceptance among males and people with higher educational qualification. Conclusions: This research results can be actively used in population segmentation into groups based on their attitudes and this understanding which can be used to develop targeted behavior change communication in improving vaccine acceptance campaigns.